UNIVERSITY BASED SENIOR CENTER - Karina, Shifa
The increase in life expectancy confronts Indonesia with the phenomenon of population aging. In 2045, it is projected that the number of elderly people in Indonesia will reach 19.8% or almost one fifth of the total population. Therefore, it is an important concern for the government, stakeholders, and the community to support the elderly population so that they can keep staying healthy, active, and independent in their old age. For this reason, the practice of Active Aging principles is very important, namely by optimizing health, participation, and safety for the elderly. However, the government's attention to the needs of the elderly's social participation is still lacking. Based on WHO Age Friendly City parameters, the needs of elderly population living in Depok City are still lacking within the dimensions of Civil & Employment Participation and the dimensions of Respect & Social Inclusion. The university with its principle, Tri Dharma Perguruan Tinggi, can mediate by establishing an elderly facility with programs aimed at increasing opportunities for elderly’s social, health, educational, and employment needs. It is hoped that the facility could elevate activity, social participation, and positive contributions within the elderly population. The main goal is to assist the new generation of elderly in maintaining their empowerment. The design process started with conducting a literature study, survey, and observation. The data obtained were analyzed through programming to answer the problem. The design concepts applied in this project are safe, comfortable and peaceful. Safe through Universal Design principles, comfortable through the formation of a sense-of-home, and peaceful through biophilic design. Furthermore, the design process is carried out until the creation of a comprehensive facility design.